Polymerase chain reaction for screening clinical isolates of corynebacteria for the production of diphtheria toxin. Issue 4 (April 1994) - Pallen, M J; Hay, A J; Puckey, L H; Efstratiou, A
Abstract : AIMS–To assess the performance of the polymerase chain reaction (PCR) when used to screen rapidly large numbers of corynebacteria for toxin production; and to determine the incidence of false positive PCR results with non-toxigenic Corynebacterium diphtheriae isolates. METHODS–Eighty seven recent British isolates of corynebacteria were assayed by PCR. All isolates were assayed from both blood and tellurite agar within a five day period. Thirty three non-toxigenic isolates of C diphtheriae from six countries were also tested by PCR and by the Elek immunodiffusion assay. RESULTS–There was complete concordance between the results of PCR and traditional methods on the recent British isolates, with one exception: an Elek positive "C ulcerans" isolate, which was PCR positive from tellurite but not from blood agar. One of the thirty three (3%) non-toxigenic isolates of C diphtheriae was PCR positive. CONCLUSIONS–These results suggest that PCR compares favourably with traditional methods for the detection of toxigenic corynebacteria and that it represents a powerful new tool in the diagnosis of an old disease.